Do steroid injections to the peripheral nerve increase perineural fibrosis? An animal experimental study - Çeliktaş, Mustafa; Olguner, Semih Kivanc; Erdogan, Kivilcim; Çaylak, Remzi; Dağlıoğlu, Kenan (Journal of Surgery and Medicine, 2022)
Background/Aim: Perineural fibrosis may be seen in some surgeries after unsuccessful transforaminal injections. This animal experiment aims to investigate the effect of steroids and/or local anesthetic substances used in epidural/transforaminal injections on fibrosis. Methods: A total of 14 male Wistar-Albino rats were separated into two groups of 7. After intraperitoneal anesthesia, right and left sciatic nerves were explored in all groups. In group 1, appropriate dose of methylprednisolone acetate and bupivacaine hydrochloride, and in group 2 only methylprednisolone acetate was administered to the explored left sciatic nerves. The right sciatic nerves were identified and explored without the application of any procedure to secure the control side of the groups. All explored areas were marked for later sampling. After 3 weeks, rats were sacrificed and samples were taken around the sciatic nerve for histopathological examination. Results: In group 1, perineural fibrosis around the left sciatic nerve (intervention side) was seen at grade 3 in five rats and at grade 0 in two. In right sciatic nerve as the control side, grade 2 fibrosis was observed in 5 rats, and fibrosis was not observed in two rats. No statistically significant difference was defined with respect to perineural fibrosis (P=0.128). In group 2, perineural fibrosis was seen around the left sciatic nerve (intervention side) at grade 3 in 5 rats, at grade 4 in one rat, and not observed in one rat. In the control side of the second group, perineural fibrosis was seen at grade 3 and 1 in one each, and was not seen in five rats. The difference between intervention side and control side in the rate of perineural fibrosis seen was statistically significant (P=0.026). Conclusions: The application of steroids alone to the nerve was determined to increase the risk of perineural fibrosis development. The addition of local anesthetics to the steroid in the injection may reduce the possibility of perineural fibrosis.